Dystrophin and utrophin "double knockout" dystrophic mice exhibit a spectrum of degenerative musculoskeletal abnormalities. Issue 3 (23rd October 2012) - Isaac, Christian; Wright, Adam; Usas, Arvydas; Li, Hongshuai; Tang, Ying; Mu, Xiaodong; Greco, Nicholas; Dong, Qing; Vo, Nam; Kang, James; Wang, Bing; Huard, Johnny
Abstract Duchenne muscular dystrophy (DMD) is a degenerative muscle disorder characterized by the lack of dystrophin expression at the sarcolemma of muscle fibers. In addition, DMD patients acquire osteopenia, fragility fractures, and scoliosis indicating that a deficiency in skeletal homeostasis coexists but little is known about the effects of DMD on bone and other connective tissues within the musculoskeletal system. Recent evidence has emerged implicating adult stem cell dysfunction in DMD myopathogenesis. Given the common mesenchymal origin of muscle and bone, we sought to investigate bone and other musculoskeletal tissues in a DMD mouse model. Here, we report that dystrophin–utrophin double knockout (dko) mice exhibit a spectrum of degenerative changes, outside skeletal muscle, in bone, articular cartilage, and intervertebral discs, in addition to reduced lifespan, muscle degeneration, spinal deformity, and cardiomyopathy previously reported. We also report these mice to have a reduced capacity for bone healing and exhibit spontaneous heterotopic ossification in the hind limb muscles. Therefore, we propose the dko mouse as a model for premature musculoskeletal aging and posit that a similar phenomenon may occur in patients with DMD. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 343–349, 2013